2019
DOI: 10.1098/rsbl.2019.0626
|View full text |Cite
|
Sign up to set email alerts
|

Eco-evolutionary feedbacks link prey adaptation to predator performance

Abstract: Eco-evolutionary feedbacks may determine the outcome of predator–prey interactions in nature, but little work has been done to quantify the feedback effect of short-term prey adaptation on predator performance. We tested the effects of prey availability and recent (less than 100 years) prey adaptation on the feeding and growth rate of largemouth bass ( Micropterus salmoides ), foraging on western mosquitofish ( Gambusia affinis ). Field surveys showed higher dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Finally, we observed a transient unfolding of the EETCs, with effects lagging in time for populations distantly removed from the initial impact to the top predator. In combination with other recent results [11], our results extend the discussion of eco-evolutionary dynamics, often focused on feedbacks between directly interacting species [50,51,59,60], to cascading effects to indirectly interacting populations [11,16], providing a potentially useful expansion of our understanding about how trophic cascades work. For example, EETCs may help us understand empirical patterns such as the different degrees of body size decline in fishes of different trophic levels in the northwest Atlantic [61].…”
Section: Discussionsupporting
confidence: 77%
“…Finally, we observed a transient unfolding of the EETCs, with effects lagging in time for populations distantly removed from the initial impact to the top predator. In combination with other recent results [11], our results extend the discussion of eco-evolutionary dynamics, often focused on feedbacks between directly interacting species [50,51,59,60], to cascading effects to indirectly interacting populations [11,16], providing a potentially useful expansion of our understanding about how trophic cascades work. For example, EETCs may help us understand empirical patterns such as the different degrees of body size decline in fishes of different trophic levels in the northwest Atlantic [61].…”
Section: Discussionsupporting
confidence: 77%
“…The study of mosquitofish traits after their introduction into novel conditions has consistently demonstrated their capacity for rapid trait changes. By comparing invasive populations that share recent common ancestors, studies have shown significant among‐population variation in traits like environmental tolerance (Vinson et al., 1963; Meffe et al., 1995 EM; Stockwell & Vinyard, 2000 WM; Annabi et al., 2009 WM), life history (Kahn et al., 2013; Stearns, 1983a EM), metabolism (Moffett et al., 2018 WM), antipredator traits (Fryxell et al., 2019 WM) and morphology and behaviour (Ouyang et al., 2018 WM; Wood et al., 2019 WM). In some cases, this interpopulation trait variation has been shown to have a genetic basis (Stearns, 1983b; Meffe et al., 1995 EM; Stockwell & Weeks, 1999 WM; Fryxell et al., 2020 WM), highlighting the speed of evolutionary changes that may commonly occur in nature (Hairston et al., 2005; Hendry et al., 2008).…”
Section: Mosquitofish As a Model Systemmentioning
confidence: 99%
“…These strong trophic effects potentially make mosquitofish useful in tying ongoing or recent trait changes to ongoing or recent ecosystem changes, as is the goal in the burgeoning field of eco‐evolutionary dynamics (Hendry, 2016). Intraspecific variation among mosquitofish populations has been shown to have substantial ecosystem consequences (Fryxell & Palkovacs, 2017 WM; Wood et al., 2019 WM, Wood et al, 2020a, 2020b WM; Fryxell, Wood, et al., 2019 WM), although the relative contribution of evolution versus plasticity to these effects merits future investigation.…”
Section: Mosquitofish As a Model Systemmentioning
confidence: 99%
“…Growth-survival tradeoffs facilitate prey evolution by tying prey traits to predator densities. When predators are abundant, prey may evolve defenses that enhance survival (at a cost to growth), driving down predator abundances [2]. When predator abundances are low and competition between prey increases, prey may evolve increased growth at a cost to survival [23], allowing predator abundances to climb.…”
Section: Introductionmentioning
confidence: 99%